Presentaciones OSIPTEL - Reunión Nº 36 de APECTEL - CHILE - Thornberry Villarán, Guillermo (2007)
Promotion of the “Andean backbone” as an alternative carrier system to reduce transport costs for rural operators. Identification of favorable scenarios to implement telecommunications projects which will use innovative technologies such as the ones that use electric energy to support telecommunications networks and services.